Permafrost and periglacial processes in mid‐ and low‐latitude mountain regions. (4th December 2019) - Ruiz‐Fernández, Jesús; Oliva, Marc; Hughes, Philip
Abstract: The Special Issue that justifies this Editorial has been designed to commemorate the 25th anniversary of the first Spanish scientific meeting of the International Permafrost Association organized in 1994 in Madrid. This Special Issue, entitled "Permafrost and periglacial processes in mid‐ and low‐latitude mountains regions, " includes nine papers from various mountain regions around the world, such as the Pyrenees, Sierra Nevada, Galician and Cantabrian Mountains in the Iberian Peninsula, Atacama and Central Andes in South America, Absaroka ranges in North America, and Seckauer Tauern Range in the European Alps. These articles provide new methodologies and approaches focusing on a wide range of periglacial phenomena, such as past cryogenic environments, active periglacial processes, permafrost and ground thermal regime, as well as rock glaciers. As a result of this Special Issue, we have detected several knowledge gaps that should be addressed in the future by the scientific community studying permafrost and periglacial processes in mid‐ and low‐latitude mountains regions, namely: (a) improving the geochronology of past periglacial environments and associated paleoclimatic implications; (b) the study of periglacial features existing in low‐altitude mountain environments and/or in the lowlands; (c) improve our current knowledge of active periglacial processes, permafrost distribution and ground thermal regime in mid‐altitude mountains; (d) the monitoring of periglacial mass wasting processes and mechanisms of sediment transfer; (e) the interaction between glaciers and periglacial processes; and (f) geoecological dynamics in response to climate scenarios anticipating significant changes of temperature and moisture in periglacial regions.